Prebiotic potential of banana and red dragon fruit peel / Siti Liyana Haziqah Hamidon - Hamidon, Siti Liyana Haziqah (Faculty of Applied Sciences, 2014)
The aim of this study was to identify the potential of the peel from the banana (Musa acuminate colla) and red dragon fruit (Hylocereus polyrhizes) as prebiotic and also to analyse the sugar content from both of the peels. The steps involved in this study were sample preparation and extraction by using the soxhlet extraction, rotary evaporator, prebiotic activity assay using the Lactobacillus sp. isolated from the cultured drink, determination of the sugar composition by using the dinitrosalicyclic assay (DNS) and fructose assay and measured by comparison with the standard curve of glucose and fructose. In this study, it was found that both banana and red dragon fruit peels has a potential source of prebiotics due to its capabilities to stimulate the growth of probiotic strain that was Lactobacillus sp. The increasing number of microbial counts between both samples showed no significant differences at (p≤0.05). Next, for the determination of glucose using the DNS assay, it was found that the glucose concentration was the highest in banana peel meanwhile for the fructose determination, the highest fructose concentration was in the red dragon fruit peel. It can be concluded that both peel have benefits and can be used as prebiotic.